2003
DOI: 10.1007/s00270-003-0023-z
|View full text |Cite
|
Sign up to set email alerts
|

Accessory Meningeal Arterial Supply to the Posterior Nasal Cavity: Another Reason for Failed Endovascular Treatment of Epistaxis

Abstract: A patient with intractable posterior epistaxis was treated with embolization of the ipsilateral sphenopalatine and facial arteries and contralateral sphenopalatine artery. She continued to bleed despite a seemingly adequate embolization procedure. A second angiogram revealed a significant collateral blood supply to the posterior nasal cavity from the accessory meningeal artery not identified during the first procedure. This was then embolized with no further epistaxis encountered. This case demonstrates yet an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Rarely, the accessory meningeal artery supplies the posterior part of the nasal cavity. This fact has to be kept in mind while treating intractable posterior epistaxis with embolization of the ipsilateral sphenopalatine and facial arteries and contralateral sphenopalatine artery (Duncan & Dos Santos, 2003). Auriculotemporal nerve is a branch of the posterior division of the mandibular nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Rarely, the accessory meningeal artery supplies the posterior part of the nasal cavity. This fact has to be kept in mind while treating intractable posterior epistaxis with embolization of the ipsilateral sphenopalatine and facial arteries and contralateral sphenopalatine artery (Duncan & Dos Santos, 2003). Auriculotemporal nerve is a branch of the posterior division of the mandibular nerve.…”
Section: Discussionmentioning
confidence: 99%
“…i) Accessory meningeal arteries may also rarely be a source of bleeding in epistaxis and can be embolized. 25 j) A review of embolization compared to internal maxillary ligation suggested that ligation was more effective and, although the complications were more frequent than for embolization, the major complications of embolization (stroke) were more serious. except in cases when an obvious major neurological de fi cit will result.…”
Section: 3 Tips On Specific Disease Processes Extracranial Embolizmentioning
confidence: 97%
“…The artery also supplies the posterior nasal cavity and can be a source of nasal bleeding. 62 The intracranial contribution is usually small and enters the skull through foramen ovale (most commonly) or the sphenoidal emissary foramen of Vesalius (in 22% of cases). 60 The intracranial rami supply the meninges of variable portions of the middle cranial fossa, portions of the cavernous sinus and the trigeminal nerve and its ganglion.…”
Section: ) Branchesmentioning
confidence: 99%